2005
DOI: 10.1124/jpet.105.087809
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the 5-Hydroxytryptamine (5-HT)1AReceptor Inverse Agonists Rec 27/0224 and Rec 27/0074 on Electrophysiological Responses to 5-HT1AReceptor Activation in Rat Dorsal Raphe Nucleus and Hippocampus in Vitro

Abstract: The pharmacological properties of cyclohexanecarboxylic acid, {2-[4-(2-bromo-5-methoxybenzyl)piperazin-1-yl]ethyl}-(2-trifluoromethoxyphenyl)amide (Rec 27/0224), and cyclohexanecarboxylic acid, (2-methoxy-phenyl)-{2-[4-(2-methoxyphenyl)-piperazin-1-yl]ethyl}amide (Rec 27/0074), were characterized using radioligand displacement and guanosine 5Ј-O-(3- -{2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl}-N-2-pyridinylcyclo-hexanecarboxamide (WAY-100635).Impairment of 5-hydroxytryptamine (5-HT) neurotransmission is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The PAG receives serotonergic projections from the dorsal raphe nuclei (see Millan 2003, for review), and activation of 5HT1A receptors promotes the control of anxiety states and the hypothalamus-pituitary-adrenal axis during stress responses (Carrasco and Van de Kar 2003). Corroborating the proposal that CBD could facilitate 5HT1A-mediated neurotransmission, its anxiolytic effect in the dlPAG was prevented by previous treatment with WAY100635, a highaffinity (Ki ranging from 0.1 to 2.2 nM, Hamon et al 1990, Corradetti et al 2005) 5HT1A receptor antagonist. The dose of WAY100635 was the same that was able to block the anxiolytic effects of 8-OH-DPAT, a 5HT1A agonist, in the dlPAG (Zanoveli et al 2003;De Paula Soares and Zangrossi 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The PAG receives serotonergic projections from the dorsal raphe nuclei (see Millan 2003, for review), and activation of 5HT1A receptors promotes the control of anxiety states and the hypothalamus-pituitary-adrenal axis during stress responses (Carrasco and Van de Kar 2003). Corroborating the proposal that CBD could facilitate 5HT1A-mediated neurotransmission, its anxiolytic effect in the dlPAG was prevented by previous treatment with WAY100635, a highaffinity (Ki ranging from 0.1 to 2.2 nM, Hamon et al 1990, Corradetti et al 2005) 5HT1A receptor antagonist. The dose of WAY100635 was the same that was able to block the anxiolytic effects of 8-OH-DPAT, a 5HT1A agonist, in the dlPAG (Zanoveli et al 2003;De Paula Soares and Zangrossi 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In this physiological assay, the two inverse agonists fully antagonized the effect of 5-CT applications on dorsal raphe neurons but with a much slower time course to reach steady state than would have been expected from their binding affinities at 5-HT 1A receptors, or compared with the time course to reach steady state with the neutral antagonist WAY100,635. Corradetti et al (2005) suggested that this phenomenon may be explained by a slow allosteric shift of the receptor toward an inactive state. Moreover, in contrast to WAY100,635, which could fully antagonize 5-CT-induced hyperpolarization of hippocampal CA1 neurons, these two compounds showed only partial antagonism, suggesting that these drugs may behave differentially on neuronal populations expressing either pre-or postsynaptic 5-HT 1A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inverse agonists may produce more prominent receptor upregulation than neutral antagonists (Adan and Kas, 2003), and inverse agonists may lead to increases in G-protein expression levels (Kenakin, 2004). A recent electrophysiological study assessed the effect of two selective 5-HT 1A inverse agonists (Rec 27/0224 and Rec 27/0074) on hippocampal and dorsal raphe neurons (Corradetti et al, 2005). In this physiological assay, the two inverse agonists fully antagonized the effect of 5-CT applications on dorsal raphe neurons but with a much slower time course to reach steady state than would have been expected from their binding affinities at 5-HT 1A receptors, or compared with the time course to reach steady state with the neutral antagonist WAY100,635.…”
Section: Discussionmentioning
confidence: 99%
“…NPY-containing neurons, including those in the ARC, express 5-HT 1A and 5-HT 1B receptors (Guptarak, Selvamani, & Uphouse, 2004), which are known to mediate 5-HT inhibitory effects in other brain areas (Rhee, Ishibashi, & Akaike, 1996;Stanford, Kantaria, Chahal, Loucif, & Wilson, 2005). As WAY-100635 demonstrates high affinity to the 5-HT 1A receptor (de Boer & Koolhaas, 2005), we utilized a dose of 1 µM, together with 30 µM of 5-HT, consistent with prior studies (Corradetti et al, 2005) the direct inhibition by 5-HT in the present study. The stimulatory effect of 5-HT in the lateral ARC has not been previously described.…”
Section: ) the Inhibitory Effects Of 5-ht In Both The Arc And Vmh Arementioning
confidence: 74%